2005
DOI: 10.1002/tea.20070
|View full text |Cite
|
Sign up to set email alerts
|

Confronting prospective teachers' ideas of evolution and scientific inquiry using technology and inquiry-based tasks

Abstract: This study addresses the need for research in three areas: (1) teachers' understandings of scientific inquiry; (2) conceptual understandings of evolutionary processes; and (3) technology-enhanced instruction using an inquiry approach. The purpose of this study was to determine in what ways The Galapagos Finches software-based materials created a context for learning and teaching about the nature of scientific knowledge and evolutionary concepts. The research used a design experiment in which researchers signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 46 publications
(71 reference statements)
5
71
0
5
Order By: Relevance
“…Although many of these misconceptions about natural selection are formed early in life (Evans 2000;Samarapungavan and Wiers 1997;Beardsley 2004), students in high school, college, and even graduate school often retain their misconceptions despite receiving formal training in biology (Brumby 1984;Lawson and Thompson 1988;Bishop and Anderson 1990;Ferrari and Chi 1998;Crawford et al 2005;Nehm and Reilly 2007;Robbins and Roy 2007). These confusions can inhibit understanding of related biological concepts (Greene 1990;Jensen and Finley 1996) and likely limit students′ ability to explain and comprehend other relevant phenomena such as antibiotic resistance in bacteria, impacts of climate change, or biological engineering.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although many of these misconceptions about natural selection are formed early in life (Evans 2000;Samarapungavan and Wiers 1997;Beardsley 2004), students in high school, college, and even graduate school often retain their misconceptions despite receiving formal training in biology (Brumby 1984;Lawson and Thompson 1988;Bishop and Anderson 1990;Ferrari and Chi 1998;Crawford et al 2005;Nehm and Reilly 2007;Robbins and Roy 2007). These confusions can inhibit understanding of related biological concepts (Greene 1990;Jensen and Finley 1996) and likely limit students′ ability to explain and comprehend other relevant phenomena such as antibiotic resistance in bacteria, impacts of climate change, or biological engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Robbins and Roy (2007) developed an inquiry-based teaching unit that yielded drastic improvements in college student explanations and overall acceptance of modern evolutionary theory. Recently, interactive computer-based simulations designed to support student and teacher training in biology have also successfully improved learner understanding of biological concepts and dispelled common learner misconceptions (Crawford et al 2005;Meir et al 2005a;Kara and Yesilyurt 2007;Perry et al 2008). This approach may prove to be particularly useful, as it can increase student access to expert knowledge and offer a greater flexibility in teaching situations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important that these programs be assessed to determine whether they work and, if so, how they work to improve understanding and acceptance of evolution while minimizing misconceptions (Crawford et al, 2005;McKeachie, Lin, & Strayer, 2002). This study gave insights into the lived experiences and worldview of pre-service science teachers regarding evolution.…”
Section: Suggestions For Further Studymentioning
confidence: 99%
“…The review of literature also showed that a number of studies were conducted on the student teachers studying in the pre-service (Gitlin et al, 1999;Haefner, 2004;Joram, 2007;Newman et al, 2004;Richardson & Liang, 2008;Van der Linden et al, 2012) and elementary (Volkmann, Abell & Zgagacz, 2005) and secondary science teacher education programs (Crawford, Zembal-Saul, Munford, & Friedrichsen, 2005) and with the student teachers studying history (Pendry and Husbands, 2000), geography (Spronken-Smith et al, 2008), chemistry and biology (Sozbilir, 2007), and science (Demir & Abell, 2010).…”
Section: Inquiry In Teacher Educationmentioning
confidence: 99%